Self-medication Practice among Health Sciences Undergraduate Students in Sana'a City-Yemen - Ibrahim, Doa'a Anwar; Halboup, Abdulsalam (Phcog.Net, 2019)
Background: The self-medication practice (SM) has increased worldwide for treating mild ailments without medical consultation and drug prescription. Health information background and proper SM may have positive outcomes. This study is focused on the SM practice among the undergraduate health science students either medicine or paramedical students in different education levels in Sanaa City. Methods: A prospective cross sectional questionnaire was structured and validated to conduct randomly a sample of health science undergraduate students from January to April 2019 in Sanaa City-Yemen. Chi-square test and logistic regressions were the analytical methods used in this study. A 468-health science students involved in this study for 4 months form from January 2019 to April 2019. Results: The prevalence of SM practice was 90% compared with non-self medicating respondents (10%) as outcomes of this work. Females (93%) showed significantly higher SM practice than males (87%). The mildness of the illness (90%) and prior experience (82%) were the two most frequently reported source of drug information for self-medication in this study. Cough, common cold (88%) and headache (88%) were the most likely symptoms reported as self-medicated illnesses in the present study. The most frequently consumed medications have been analgesics (87%), common cold preparations (82%) and antipyretics (78%). Self-medication practice was noticeable among health sciences undergraduate students in Sanaa city and this referred to the mildness of the illness and previous ex perience. There were statistically significant differences between respon dents based on gender in the present study, but there were differences, neither according to specific fields nor to educational level.